10 Food and nutrition security in key healthcare workers during the first wave of the COVID-19 pandemic: a case study informing educational interventions. (18th October 2022) - Bradfield, James; Jaffee, Ally; Broadley, Iain; Ray, Sumantra
Abstract : Background: The COVID-19 pandemic brought food and nutrition security to the fore in many sectors like never before. It altered purchasing behaviours in the United Kingdom, including that of food and other essential products. This survey sought to identify how the pandemic changed behaviours of specific populations. The primary targets were healthcare professionals working in the National Health Service (NHS) while a secondary target were students training to work in the NHS. Objectives: To assess how the first wave of the COVID-19 pandemic affected food choices and eating behaviours of frontline healthcare staff and students. Methods: A semi-qualitative, online survey was conducted to gain an understanding of the challenges faced during the pandemic, in a manner that can inform a future blueprint on occupational nutrition education for healthcare professionals. As a semi-qualitative survey, it sought to describe subjective experiences and recognise patterns or recurring themes. The participants were either healthcare professionals in the NHS or students training to be healthcare professionals in the NHS. Results: Many in the survey commented on choosing quick options that would save them time while others made use of techniques such as batch cooking and freezing meals for later. They called for an end to stockpiling of materials, a trend seen frequently in the first wave of the pandemic. This survey indicated that overall, frontline workers and healthcare students have significantly changed their food choices and eating behaviours during the course of the first wave of the pandemic. Based on these insights, an educational intervention can be designed to educate such workers on the importance of good nutrition as well as practical tips to achieve this in times of pressure. This may be evaluated using a knowledge, attitudes and practices (KAP) before and after design. Conclusion: These members of the healthcare community would benefit from micro-training emphasizing how to make simple, nutritious meals quickly, for use when external circumstances alter their habits and access to food. Furthermore, they would benefit form a comprehensive governmental occupational health strategy to optimize nutrition and pandemic resilience.